The influence of animal ownership on mental health for people with severe mental illness: Findings from a UK population cohort study - Emily Shoesmith; Ben Lorimer; Emily Peckham; Lauren Walker; Elena Ratschen (Human-Animal Interactions, 2023)
Abstract Background and aims: There is increasing evidence to suggest companion animal ownership may positively impact mental health and wellbeing. However, there is limited research related to the role of companion animal ownership for mental health that focuses on people living with severe mental illness (SMI). We aimed to explore the connection among loneliness, mental health, wellbeing, animal ownership, and the perceived strength of the human-animal bond in this population. Methods: We conducted a survey in an existing UK cohort of people living with SMI. The survey questionnaire included standardized measures to collect information related to mental health, loneliness, and the perceived strength of the human-animal bond. Results: Of 286 participants who had previously consented to participate in the follow-up survey, 170 participants (59.4%) completed the survey. Of these, 81 (47.6%) owned at least one animal, and most perceived to have a strong human-animal bond with their companion animal as indicated by the Comfort from Companion Animals Scale (M = 39.80 of a maximum score of 44). However, regression analyses showed that owning an animal was not significantly associated with wellbeing, depression, anxiety, or loneliness scores. Likewise, the perceived strength of the human-animal bond was not significantly associated with animal species owned or wellbeing, depression, and anxiety scores. Conclusion: The findings provide a counterpoint to the commonly held assumption that companion animals are beneficial for all owners’ mental health. Further exploration of the role of human-animal relationships, including challenges and support needs related to animal ownership, in people living with SMI is required.